2011
DOI: 10.1163/001121611x584361
|View full text |Cite
|
Sign up to set email alerts
|

Growth Parameters and Population Structure of Aristeus Antennatus (Decapoda, Penaeidae) in the South Tyrrhenian Sea (Southern Coast of Italy)

Abstract: The blue and red shrimp Aristeus antennatus (Risso, 1816) is one of the most important fishery resources in the Mediterranean Sea. Monthly samplings of blue and red shrimp from June 2006 to May 2007 were landed by the trawl fleet in two northwest Sicilian fishing harbours (San Vito Lo Capo and Terrasini). The carapace length (CL) frequency distribution of females ranged between 15.00 and 59.00 mm, whereas male CLs ranged between 17.00 and 34.00 mm. The estimated parameters of the Von Bertalanffy growth functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Related to the MPA analysis (Table 2), the number of estimated age groups and the size of each group was quite similar to data reported by other studies conducted close to our area of study (Table 3), i.e., Gulf of Alicante, Gulf of Vera and Balearic Islands, [34,53,54]. However, our data do not differ substantially from other studies conducted in more remote areas either, i.e., Ligurian, Tyrrhenian, and Ionian Seas [23,[30][31][32]. Indeed, the largest size-age ratio differences between groups were observed in older age groups, approximately from 4+ onwards, in which it becomes difficult to distinguish the cohorts due to age-related reduction of growth rate [34].…”
Section: Size-age Composition and Commercial Categories Of A Antennat...supporting
confidence: 90%
“…Related to the MPA analysis (Table 2), the number of estimated age groups and the size of each group was quite similar to data reported by other studies conducted close to our area of study (Table 3), i.e., Gulf of Alicante, Gulf of Vera and Balearic Islands, [34,53,54]. However, our data do not differ substantially from other studies conducted in more remote areas either, i.e., Ligurian, Tyrrhenian, and Ionian Seas [23,[30][31][32]. Indeed, the largest size-age ratio differences between groups were observed in older age groups, approximately from 4+ onwards, in which it becomes difficult to distinguish the cohorts due to age-related reduction of growth rate [34].…”
Section: Size-age Composition and Commercial Categories Of A Antennat...supporting
confidence: 90%
“…Previous studies have shown that an understanding of the parameters of growth and of the population structure of decapod crustaceans is fundamental for a better understanding of the biology and life cycle of these species (FONSECA; D' INCAO, 2003;KEUNECKE et al, 2007;LOPES-LEITZKE et al, 2009;ARCULEO et al, 2011). Thus, the goal of this study is to discern the patterns of the population dynamics of Acetes americanus -particularly the sex ratio, growth of individual specimens, longevity, and recruitment -in terms of the abundance of species and the influence of environmental factors in the region of Macaé, RJ.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the individual growth of crustaceans have been reported in the literature estimating age in relation to the size (Kirkwood and Sommers, 1984;Die, 1992;D'Incao and Fonseca, 1999;Pérez-Castañeda and Defeo, 2005). Previous studies (Fonseca and D'Incao, 2003;Dumont and D'Incao, 2004;Keunecke et al, 2007;Lopes-Leitzke et al, 2009;Arculeo et al, 2011) have demonstrated that understanding patterns in the growth and structure of crustacean populations is fundamental for deriving the life history necessary for the effective and sustainable management of these species. However, little information is available regarding the population parameters of Acetes, with the exception of studies by Zafar and Amin (2002), Oh and Jeong (2003) and Amin et al (2008Amin et al ( , 2009aAmin et al ( , 2009b.…”
Section: Introductionmentioning
confidence: 99%